Regenerated Silk and Carbon Nanotubes Dough as Masterbatch for High Content Filled Nanocomposites - Valentini, Luca; Bittolo Bon, Silvia; Tripathi, Manoj; Dalton, Alan; Pugno, Nicola M. (Frontiers in Materials, 2019)
Regenerated silk (RS) is a natural polymer that results from the aggregation of liquid proteins. In this work we observed that RS dispersed in aqueous solution undergoes to a reversible solid/liquid transition by programmed heating/cooling cycles. Fourier transform infrared (FTIR), atomic force microscopy imaging and Raman measurements of the RS reveal that the transition from random coil to -sheet structures is involved in this liquid–solid transition. The reversible solid-liquid transition of silk fibroin was then found helpful to prepare polymer-like carbon nanotube (CNT) dispersions. We demonstrate that the gelation of RS makes the CNTs with the consistency of a dough with polymeric behaviour. Such RS can disperse carbon nanotubes at high concentrations of tens of weight percent. Finally, such carbon nanotube dough has been used for the realization of rubber composites. With this method, we pave the way for handling powders with safety and reducing the filler volatility that is critical in polymer-processing.